2021
DOI: 10.3947/ic.2021.0015
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Antimicrobial Resistance Levels of ESKAPE Microorganisms in a Peruvian IV-Level Hospital

Abstract: Backgound The members of the so-called ESKAPE group ( Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa and Enterobacter spp.) are a frequent cause of severe infection, ranking among the most relevant causes of hospital infections. In Peru, few studies, often focused in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
(55 reference statements)
0
15
0
1
Order By: Relevance
“…The median (IQR) length of hospital stay and preoperative Model for End-Stage Liver Disease (MELD) score prior to LT were 9 (1-24) days and 24 (16-30), respectively. Eighty-one (35.4%) patients received antibiotics within 2 weeks prior to LT. One hundred (43.7%) patients were infected within 2 months but not within 2 weeks before LT. [19,20]. Seventy-ve (90.4%) of 83 E 2 SKAPE isolates were MDR which was higher than another Chinese study performed on burn patients with the rate being 55% [21].…”
Section: General Characteristics and Prognosis Of Lt Recipientsmentioning
confidence: 71%
“…The median (IQR) length of hospital stay and preoperative Model for End-Stage Liver Disease (MELD) score prior to LT were 9 (1-24) days and 24 (16-30), respectively. Eighty-one (35.4%) patients received antibiotics within 2 weeks prior to LT. One hundred (43.7%) patients were infected within 2 months but not within 2 weeks before LT. [19,20]. Seventy-ve (90.4%) of 83 E 2 SKAPE isolates were MDR which was higher than another Chinese study performed on burn patients with the rate being 55% [21].…”
Section: General Characteristics and Prognosis Of Lt Recipientsmentioning
confidence: 71%
“…Although the in vitro activity of most combinations may be scored as synergistic, their in vivo effectiveness remains uncertain due to the complexity of the infections such as infection site, pharmacokinetic, and pharmacodynamics characteristics of the drugs [13]. The results from genome sequences and epidemiological data of more than 1700 K. pneumoniae samples isolated from patients in 244 hospitals in 32 countries during the European Survey of Carbapenemase-Producing Enterobacteriaceae demonstrate that carbapenemase acquisition is the main cause of CR and 477 of 682 (69.9%) carbapenemase-positive isolates are concentrated in four clonal lineages (11,15, 101, 258/512) and their derivates [36], [37]. In this study, we focused on evaluating the interaction effect of certain combinations on twelve K. pneumoniae nosocomial strains belonging to the most prevalent sequence types in Bulgaria (ST11, ST15, and ST258).…”
Section: Discussionmentioning
confidence: 99%
“…Highly resistant K. pneumonia strains are a significant burden to the healthcare systems and have an important global economic impact. Effects include high mortality and morbidity rates, and recent data on the impact of AMR in the European Union (EU) have shown that >33,000 deaths and 874,541 disability-adjusted life-years [9], [11]. The most recent emergence of extensive-drug resistant (XDR, resistant to all drugs except cefepime, tigecycline (TGC), and ceftazidime-avibactam) and pandrug resistant (PDR, resistant to all drugs) K. pneumoniae is a wake-up call for us to contemplate more strategic measures to control their spread.…”
Section: Introductionmentioning
confidence: 99%
“…Care was taken to include methicillin-resistant Staphylococcus saprophyticus ( Higashide et al, 2008 ), members of the ESKAPE group ( Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , and Enterobacter spp.) ( Flores-Paredes et al, 2021 ), with the exception of Acinetobacter baumannii and Enterobacter spp. ; and methicillin-susceptible S. aureus (MSSA) ( Ham et al, 2010 ): The test strains included, Bacillus cereus (ATCC 10876), Escherichia coli (ATCC 10536), Klebsiella pneumoniae (ATCC 10031), Klebsiella oxytoca (ATCC 13182), Mycobacterium smegmatis (ATCC 21293), Pseudomonas aeruginosa (NCTC 10662), Staphylococcus aureus (ATCC 25923), S. saprophyticus (ATCC 15305), Staphylococcus epidermidis (ATCC 14990), Veillonella parvula (ATCC 10790), and Enterococcus faecium (ATCC 13048).…”
Section: Methodsmentioning
confidence: 99%